A study on structural and electronic properties of GaAs1-xNxÂ and GaAs1-xBix alloys - Aslan, Metin; Yalcin, Battal Gazi (International Journal of Physical Research, 2016)
We have performed first principles method to investigate structural and electronic properties of GaAs1-xNx and GaAs1-xBix ternary semiconductor alloy using Density Functional Theory and pseudo potential method within the Generalized Gradient Approximations and Local Density Approximation. The Zinc-Blende phase is found stable for GaAsN and GaAsBi alloys. In this study we investigate the both bowing parameters changing with Bismuth concentration in GaAsBi and Nitrogen concentration in GaAsN alloys. By using the bowing parameter of GaAsBi and GaAsN alloys we obtained the bandgap energies for all x concentrations (0 < x < 1) and lattice constant of both alloys which are important for wide range device application. For studied materials, lattice parameters and band gap energies are compared with available theoretical and experimental works.